The Arabidopsis Nα‐acetyltransferase NAA60 locates to the plasma membrane and is vital for the high salt stress response. Issue 2 (16th July 2020) - Linster, Eric; Layer, Dominik; Bienvenut, Willy V.; Dinh, Trinh V.; Weyer, Felix A.; Leemhuis, Wiebke; Brünje, Annika; Hoffrichter, Marion; Miklankova, Pavlina; Kopp, Jürgen; Lapouge, Karine; Sindlinger, Julia; et al.
Summary: In humans and plants, N‐terminal acetylation plays a central role in protein homeostasis, affects 80% of proteins in the cytoplasm and is catalyzed by five ribosome‐associated N‐acetyltransferases (NatA–E). Humans also possess a Golgi‐associated NatF ( Hs NAA60) that is essential for Golgi integrity. Remarkably, NAA60 is absent in fungi and has not been identified in plants. Here we identify and characterize the first plasma membrane‐anchored post‐translationally acting N‐acetyltransferase At NAA60 in the reference plant Arabidopsis thaliana by the combined application of reverse genetics, global proteomics, live‐cell imaging, microscale thermophoresis, circular dichroism spectroscopy, nano‐differential scanning fluorometry, intrinsic tryptophan fluorescence and X‐ray crystallography. We demonstrate that At NAA60, like Hs NAA60, is membrane‐localized in vivo by an α‐helical membrane anchor at its C‐terminus, but in contrast to Hs NAA60, At NAA60 localizes to the plasma membrane. The At NAA60 crystal structure provides insights into substrate‐binding, the broad substrate specificity and the catalytic mechanism probed by structure‐based mutagenesis. Characterization of the NAA60 loss‐of‐function mutants ( naa60‐1 and naa60‐2 ) uncovers a plasma membrane‐localized substrate of At NAA60 and the importance of NAA60 during high salt stress. Our findings provide evidence for the plant‐specific evolution of a plasma membrane‐anchored N‐acetyltransferase that is vital for adaptation to stress.